Seed transmission of Carlavirus vignae (Cowpea mild mottle virus): a hidden driver of veinal necrosis and bud blight disease in soybean (Glycine max) in India - Bhagwatkar, Dhruva Nitin; Sandra, Nagamani; Tripathi, Ankita; Dalal, Garima; Kesaratagi, Sharankumar; Saini, Manisha; Lal, Sandeep Kumar; Lal, Sanjay Kumar (Frontiers in Microbiology, 2025)
A comprehensive investigation was conducted to determine the seed transmission potential of cowpea mild mottle virus (CPMMV) associated with veinal necrosis and bud blight (VNB) disease in soybean (Glycine max) under Indian agroecological conditions during 2024 at ICAR-IARI, New Delhi. Seeds were collected from two CPMMV infected soybean genotypes, Asb-114 and AMS-2022-1 and mechanically sap inoculated cowpea genotypes Arka Samrudhi and Arka Suman. Serological testing of soybean and cowpea seeds using DAC-ELISA did not detect the virus with low absorbance values whereas RT-PCR with coat protein (CP)-specific primers confirmed the presence of CPMMV in whole seed, seed coat, cotyledons, and embryo with the amplification of 867 bp region. Grow out assays demonstrated the vertical transmission of CPMMV to the F₁ (75%) and F₂ (100%) progenies with the symptoms of necrotic spots and confirmed through RT-PCR and RT-qPCR. In parallel, cowpea genotypes were also confirmed for CPMMV infection in leaves, whole seed and seed parts by RT-PCR indicating the seed borne nature of the virus. Quantitative analysis using RT-qPCR revealed the highest viral titers in field infected soybean seeds (9.83 × 104–5.35 × 107), followed by F₁ seeds (8.60 × 104–1.40 × 106) and the lowest in cowpea seeds (3.19 × 104–1.36 × 105) harvested from mechanically sap inoculated plants. CPMMV infection significantly reduced seed quality parameters including 100-seed weight (4.32–6.66gm), germination percentage (55–81%), fresh weight and seedling vigor indices I and II in both the soybean genotypes. Biochemical analysis showed a marked elevation in H₂O₂, PAL and CAT activity while POX, SOD and total phenol content showed non-significant increases. Collectively, this study provides the definitive evidence of seed transmission of the CPMMV-VNB isolate in soybean and cowpea, highlighting its detrimental effects on seed quality and reinforcing its epidemiological importance in legume pathology.